A Review of Methods for Reduction of Polycyclic Aromatic Hydrocarbons from Waste Water and Flue Gases (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
This review describes methods which can be used for the reduction of the polycyclic aromatic hydrocarbon (PAH) emissions from wastewater and flue gases including principles of operation of the methods and studies of their effectiveness. There are discussed both methods, which nowadays are already used industrially, and their improvement opportunities as well as recent technological trends in this field. The methods have been classified into two main categories: flue gas treatment and wastewater treatment.